STUDI MENGENAI KEPUASAN KONSUMEN UNTUK MENINGKATKAN RETENSI KONSUMEN DI INSTALASI RAWAT INAP RSUD “X” - Winarsih . (STIE Pelita Nusantara Semarang, 2011)
Hospital is one of the health service facilities required by society. Customer satisfaction and customer retention are primary objective in a modern organizations. The important level of Hospital as a public sector, mainly as a service provider, drives the managers to address the quality and customer satisfaction as priority. It raises the question “How Service Quality, Hospital Image, Experiential Marketing affect companies in order to establish Customer Satisfaction and to increase the Customer Retention “ that exist especially in Region Common Hospital “X”.